An accelerating&focusing structure with combined RF focusing for heavy ion accelerator - Dyachenko, A.F.; Zaytsev, B.V.; Tishkin, S.S.; Fedeneva, Ya.N.; Shulika, N.G.; Shulika, O.N. (Вопросы атомной науки и техники, 2014)
An accelerating&focusing channel of high-current linac for heavy ions with mass-to-charge ratio A/q ≤ 20 is presented. The channel is calculated to form and accelerate an ion beam from 6 keV/nucl. up to 1 MeV/nucl. An accelerator initial part based on a RFQ that provides acceleration from 6 to 100 keV/nucl. and a pre-stripping section with combined RF focusing for final acceleration up to 1 MeV/nucl. comprises the accelerating-focusing channel. It is proposed to use an IH structure for combined focusing. Numerical simulation of beam dynamics is performed. The channel allows ion beam acceleration at currents up to 10 mA. Рассмотрен ускоряюще-фокусирующий канал сильноточного линейного ускорителя тяжелых ионов с отношением массового числа к зарядовому A/q ≤ 20. Канал рассчитан на формирование и ускорение пучка от энергии 6 кэВ/нукл. до 1 МэВ/нукл. Функционально в состав канала входит НЧУ на базе ПОКФ (энергия от 6 до 100 кэВ/нукл.) и предобдирочная секция (энергия до 1 МэВ/нукл.) с комбинированной высокочастот-ной фокусировкой. Предложена схема реализации этого типа фокусировки на базе IH-структур. Проведено численное моделирование динамики пучка. Канал позволяет ускорять пучки ионов с током до 10 мА. Розглянуто прискорюючо-фокусуючий канал сильнострумового лінійного прискорювача важких іонів з відношенням масового числа до зарядового A/q ≤ 20. Канал розраховано на формування та прискорення пучків від енергії 6 кеВ/нукл. до 1 МеВ/нукл. Функціонально до складу каналу входить ПЧП на базі ПОКФ (енергія від 6 до 100 кеВ/нукл.) та секція (енергія до 1 МеВ/нукл.) з комбінованим ВЧ-фокусуванням. Запро-поновано схему реалізації даного типу фокусування на базі IH-структур. Проведено чисельне моделювання динаміки пучків. Канал дозволяє прискорювати пучки іонів зі струмом до 10 мА.